EVALUATION OF ANTI-INFLAMMATORY AND ANALGESIC POTENTIAL OF AQUEOUS METHANOLIC EXTRACT OF THUJA ORIENTALIS IN ALBINO RATS - M. Z. Tanveer; A. Javeed1; M. Ashraf; M. U. Rehman; S. M. M. Anjum (Journal of Animal and Plant Sciences, 2015)
This study was conducted for evaluating a natural source to treat inflammation and pain, to avoid the severe side effects of currently used agents for these ailments. Thuja Orientalis (More Pankh) is commonly used for the treatment of pain and inflammatory disorders in traditional medicine. Carrageenan induced inflammatory model, acetic acid induced writhing test and hot plate methods were used to evaluate anti-inflammatory, peripheral and central analgesic properties of aqueous methanolic extract of Thuja Orientalis fruit (To-Cr) in albino rats. Completely randomized design (CRD) was constructed for the study and one way ANOVA was applied to compare means. The results showed that TO-Cr has significant anti-inflammatory and analgesic properties.
Keywords: Analgesic; inflammation; oedema; anti-inflammatory; carrageenan; Thuja Orientalis